Effect of season on production and quality of milk of crossbred dairy cows at Sylhet district government dairy farm in Bangladesh (Bangladesh Journal of Animal Science, 2017)
The present study was conducted to investigate the seasonal effect on milk production and milk qualities of crossbred dairy cows at DGDF, Sylhet. For these purposes, the data of milk production and milk samples were collected from bulk milk tank at District Govt. Dairy Farm, Sylhet and their qualities were measured by physico-chemical and microbiological tests. The season has a significant effect (p